Psychological Factors in Evaluation and Treatment of Diabetes - Delamater, Alan M (My University, 2017)
Both type 1 and type 2 diabetes are increasing in incidence world-wide and being diagnosed at earlier ages. Despite advances in medical treatments and technologies, most patients do not attain optimal glycemic control, many are not on intensified insulin regimens, regimen adherence problems are common, and significant diabetes-related morbidity contributes to reduced quality of life, early mortality, and substantial heath care costs to society. This presentation summarizes research on psychological problems among adults with diabetes. Studies indicate that depression, anxiety, and eating disorders are common and associated with increased risk for metabolic control problems. Research also indicates that neurocognitive problems may develop in older adults with chronic poor glycemic control. Cognitive behavior therapy has been shown to improve outcomes for patients with psychological problems, and intervention research to increase patient empowerment has also demonstrated improved patient outcomes in terms of both quality of life and glycemic control. Future research needs and recommendations for clinical care are discussed. The patient-centered chronic care model is described as a skillful approach to increase the probability of successful management of psychological problems in adults with diabetes.
Keywords: Diabetes; Evaluation; Treatment